Hall Effects On Mhd Convective Flow Through Porous Medium Past An Infinite Vertical Plate With Soret Effect And Dissipation - K. Komala, M.Mohan Babu, C.K. Selvi (International Journal of Control and Automation, 2019)
We have studied the combined effects of MHD mixed convective two-dimensional flow of an incompressible and electrically conducting viscous fluid through porous medium past an infinite vertical plate taking Soret, Joules dissipations and Hall effects into account. The non-dimensional equations are then solved analytically using perturbation technique. With the help of graphs, the effects of the various non-dimensional parameters on velocity, temperature and concentration distributions within the boundary layer are examined. Also the effects of the pertinent parameters on the skin-friction coefficient and rates of heat and mass transfer in terms of the Nusselt and Sherwood numbers are computationally discussed.